PENDAMPINGAN PENGEMBANGAN EKOWISATA MANGROVE DI PANTAI BANCARAN BANGKALAN - Herlina Fitrihidajati; Fida Rachmadiarti; Tarzan Purnomo; Reni Ambarwati (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
Abstract Mangrove ecotourism at Bancaran Beach Bangkalan is a new destination managed by a group of tourism-aware youth (Pokdarwis) with topography of mangrove, estuary and sea. Observation results showed that the facilities and infrastructure in this new ecotourism were not adequate, such as mangrove plants that don’t yet present a name so that it’s difficult to be recognized by tourists both in type and benefit and parking lots and toilets that only use the property of the RPH. The problem is the manager wants to develop it but doesn't have a plan or picture yet. Therefore, it’s necessary to provide assistance by the Unesa Biology PKM Team in order to develop it so that Ecotourism is more attractive, provides comfort and educates visitors, and improves the welfare of the surrounding community. The method used in this activity includes 3 stages, namely preparation, implementation, and monitoring. In the implementation of the PKM team, they provide assistance in the form of developing a mangrove ecotourism model through inspection and inventory of vegetation as well as the facilities and infrastructure that will be developed. The resulting design can be used as a document by Pokdarwis to develop it by offering the development plan through funding assistance to BUMN or the local government. Keywords:bancaran, mangrove ecotourism, mentoring, development